2007
DOI: 10.1104/pp.107.109033
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis INOSITOL TRANSPORTER2 Mediates H+ Symport of Different Inositol Epimers and Derivatives across the Plasma Membrane

Abstract: Of the four genes of the Arabidopsis (Arabidopsis thaliana) INOSITOL TRANSPORTER family (AtINT family) so far only AtINT4 has been described. Here we present the characterization of AtINT2 and AtINT3. cDNA sequencing revealed that the AtINT3 gene is incorrectly spliced and encodes a truncated protein of only 182 amino acids with four transmembrane helices. In contrast, AtINT2 codes for a functional transporter. AtINT2 localization in the plasma membrane was demonstrated by transient expression of an AtINT2-GRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 77 publications
(87 reference statements)
6
84
0
Order By: Relevance
“…Until now, there have been no data available on the transporters facilitating uptake of D-chiro-inositol and D-pinitol by developing embryos. In vegetative tissues of Arabidopsis different forms of plasma membrane localized transporters of cyclitols have been found: AtINT4, transporting D-pinitol beside myo-inositol and AtINT2, transporting also D-chiro--inositol (Schneider et al 2007). Our experiments indicated that maturing grains of barley accumulated more cyclitols than grains of triticale and wheat (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Until now, there have been no data available on the transporters facilitating uptake of D-chiro-inositol and D-pinitol by developing embryos. In vegetative tissues of Arabidopsis different forms of plasma membrane localized transporters of cyclitols have been found: AtINT4, transporting D-pinitol beside myo-inositol and AtINT2, transporting also D-chiro--inositol (Schneider et al 2007). Our experiments indicated that maturing grains of barley accumulated more cyclitols than grains of triticale and wheat (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Indeed, the myoinositol concentration in these lines is lower than in wild-type plants, suggesting that higher Miox activity metabolizes most of the available myoinositol. Myoinositol is readily taken up by plant cells using several transporters in the plasma membrane (Schneider et al, 2007). Feeding myoinositol to leaf discs therefore strongly increases the internal concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The Os06g21900 siRNAs are predominantly expressed in 6-10 DAF grain, so could be involved in regulating a transitional step in the developmental program of the grain. The confirmed mRNA target of an Os06g21900 siRNA, Os04g43210, encodes a putative plasma membrane myoinositol transporter (closely related to Arabidopsis INOSITOL TRANSPORTER 2) (Schneider et al 2007). This protein could be involved in transport of myoinositol or its derivatives, which could act in either metabolic or signaling roles.…”
Section: Genome Research 1461mentioning
confidence: 99%